2018
DOI: 10.1021/acs.jmedchem.7b01722
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Optimization Strategies for G Protein-Coupled Receptor (GPCR) Allosteric Modulators: A Case Study from Analyses of New Metabotropic Glutamate Receptor 5 (mGlu5) X-ray Structures

Abstract: Two interesting new X-ray structures of negative allosteric modulator (NAM) ligands for the mGlu receptor, M-MPEP (3) and fenobam (4), are reported. The new structures show how the binding of the ligands induces different receptor water channel conformations to previously published structures. The structure of fenobam, where a urea replaces the acetylenic linker in M-MPEP and mavoglurant, reveals a binding mode where the ligand is rotated by 180° compared to a previously proposed docking model. The need for mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 60 publications
1
88
0
3
Order By: Relevance
“…This highly conserved Trp residue was found to be part of the activation in several class A GPCRs (Trzaskowski et al, 2012), including rhodopsin (Ahuja & Smith, 2009). Nevertheless, its conformational change is not a universal toggle of GPCR activation (Rasmussen et al, 2011), and the conformation is ligand dependent in NAM complexes (Christopher et al, 2015(Christopher et al, , 2019Dor e et al, 2014) and both conformations are accessible in activated mGluR5 in complex with 3 (PAM). Y659 3.44c is close to the varying aromatic substituent (Me/ Cl/F; Scheme 1) of the complexes studied and its analogous 3.40 residue in class A GPCRs is part of the transmission switch (Trzaskowski et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This highly conserved Trp residue was found to be part of the activation in several class A GPCRs (Trzaskowski et al, 2012), including rhodopsin (Ahuja & Smith, 2009). Nevertheless, its conformational change is not a universal toggle of GPCR activation (Rasmussen et al, 2011), and the conformation is ligand dependent in NAM complexes (Christopher et al, 2015(Christopher et al, , 2019Dor e et al, 2014) and both conformations are accessible in activated mGluR5 in complex with 3 (PAM). Y659 3.44c is close to the varying aromatic substituent (Me/ Cl/F; Scheme 1) of the complexes studied and its analogous 3.40 residue in class A GPCRs is part of the transmission switch (Trzaskowski et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The structural and functional importance of these interactions is underlined by several findings. The water molecule mediating the H-bond between Y659 3.44c and T781 6.46c is identified in all available X-ray structures of mGluR5-NAM complexes (Christopher et al, 2015(Christopher et al, , 2019Dor e et al, 2014) and the Hbond was also observed in MD simulations of the mGluR2 (P erez-Benito et al, 2017) and mGluR5 receptors in complex with NAMs (Llinas del Torrent, Casajuana-Martin, et al, 2019). Moreover, it was shown that mutations of Y659 3.44c and T781 6.46c in mGluR5 significantly impact the activity of allosteric ligands by either reducing (Gregory et al, 2014;Malherbe et al, 2006) or inverting (Turlington et al, 2013) their functional effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, two structural motifs, i.e., amide and urea functional groups, are proposed as the replacements of alkyne linkages in mGluR5 NAMs [18]. So far, altogether eight known mGluR5 NAMs have entered and/or are about to enter clinical trials, i.e., Mavoglurant [19][20][21], Basimglurant [8,21], MTEP [8], HTL14242 [20], Dipraglurant [21], Fenobam [21,22], Thiazole-2-carboxamides (6bc, 6bj) [18]. It is worth mentioning that, for a long time, the important structural information on mGluR5 NAMs was to combine mutation studies with homology modeling and/or a series of ligand analogs.…”
Section: Discussionmentioning
confidence: 99%